A case study: Eliminating nuisance within-part variation in assessing a measurement system. Issue Volume 35:Issues 1(2023) (2nd January 2023) - Hamada, M. S.; O'Brien, B. W.
Abstract: In this article, we consider a gauge R & R study in which a part measured in production is randomly placed in the measuring device. In assessing a measurement system, one does not want a possible within-part variation included in the estimated gauge variation and we propose a way to eliminate it. We consider a pellet measurement system and demonstrate the benefits of eliminating within-part variation in its assessment.